A Public Health Framework for Developing Local Preventive Services Guidelines. (January 2014) - Chu, Priscilla Lee; Nieves-Rivera, Israel; Grinsdale, Jennifer; Huang, Sandra; Philip, Susan S.; Pine, Amy; Scheer, Susan; Aragón, Tomás
In this article, we describe the San Francisco Department of Public Health's (SFDPH's) framework for developing evidence-based screening and vaccination recommendations. We first reviewed our local data using surveillance and syndemic data. We then compiled and compared existing federal, state, and local recommendations. Then we identified differences as compared with our local evidence; where more evidence was required to make a recommendation, we culled from additional data sources and conducted additional analyses. Lastly, we developed our guidelines by confirming existing recommendations or making new recommendations based on this process. In the end, we successfully developed evidence-based clinical screening and prevention guidelines that have been adopted by the SFDPH Health Commission. We encourage the use of this framework in other public health settings at the local level.